Corneal Relapse of Peripheral T-Cell Lymphoma Under Systemic Chemotherapy. Issue 12 (December 2018) - Kiratli, Hayyam; Aygün, Figen B.; Gedikoğlu, Gökhan
Abstract : Purpose: To report a patient who developed unilateral corneal stromal infiltration while undergoing systemic chemotherapy for multinodal peripheral T-cell lymphoma not otherwise specified. Methods: Clinical, imaging, and immunohistopathological features of a 40-year-old woman who presented with a stromal haze in the right cornea were reviewed. Results: At initial presentation, her visual acuity in the right eye was 20/40. Slit-lamp examination showed stromal infiltration located mainly in the inferotemporal peripheral cornea without epithelial or limbal involvement. Immunohistochemical examination of the incisional biopsy specimen revealed CD3 +, CD5 +, and CD8 − neoplastic lymphocytes suggestive of T-cell lymphoma. The corneal lesion and disseminated lymphadenopathy did not respond to various combinations of several cycles of systemic chemotherapy. Remission was achieved only after allogeneic bone marrow transplantation. The corneal infiltrates almost totally regressed within 6 months, and she maintained 20/20 visual acuity thereafter. She did not have any systemic or ocular recurrence during 6 years of posttransplantation follow-up. Conclusions: In this rare case of systemic multinodal peripheral T-cell lymphoma, corneal stromal infiltration was the only ocular manifestation. Prompt corneal biopsy enabled the appropriate diagnosis. Development and persistence of corneal infiltration despite systemic chemotherapy may be a warning sign for resistance to treatment.